2014
DOI: 10.1155/2014/495084
|View full text |Cite
|
Sign up to set email alerts
|

Development of Automatic Visceral Fat Volume Calculation Software for CT Volume Data

Abstract: Objective. To develop automatic visceral fat volume calculation software for computed tomography (CT) volume data and to evaluate its feasibility. Methods. A total of 24 sets of whole-body CT volume data and anthropometric measurements were obtained, with three sets for each of four BMI categories (under 20, 20 to 25, 25 to 30, and over 30) in both sexes. True visceral fat volumes were defined on the basis of manual segmentation of the whole-body CT volume data by an experienced radiologist. Software to automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…Abdominal CT can provide rapid and accurate assessment of the distribution of abdominal fat through subjective or objective means [31]. Firstly, abdominal CT can be used to quantify abdominal fat as android (mainly visceral and sphere shaped) or gynoid (mainly subcutaneous and ellipse shaped) [32].…”
Section: Estimation Of Intra-abdominal Volume and Compliancementioning
confidence: 99%
“…Abdominal CT can provide rapid and accurate assessment of the distribution of abdominal fat through subjective or objective means [31]. Firstly, abdominal CT can be used to quantify abdominal fat as android (mainly visceral and sphere shaped) or gynoid (mainly subcutaneous and ellipse shaped) [32].…”
Section: Estimation Of Intra-abdominal Volume and Compliancementioning
confidence: 99%
“…Nemoto et al first reported the type of software and concluded it was feasible for calculating visceral fat volumes in a rea-sonable time with high accuracy. 27 By using similar software, we avoided estimation calculations such as adding or multiplying by pixel surface area. Thus, we were able to calculate real-life adipose tissue volumes, which would not be possible using the area measurements used in most previous cancer studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue was initially segmented by thresholding the CT images between − 174 and − 24 Hounsfield Units (HU) [18,[32][33][34][35] (refer to the supplementary material for more details on fat segmentation). The abdominal muscular layer was used as a boundary to separate VAT and SAT.…”
Section: Discussionmentioning
confidence: 99%